Título Padrão: A case of dual society - Mota Gaspar, Luciano (Revista de Ciências Sociais, 2020)
The economic condition of the Northeast is frequently discussed as a problem in Brazilian studies. Some view the region as one of "two Brazils" making up a dual society; others see the Northeast as a part of a regionally stratified, but essentially unified nation. These two views will be compared and contrasted in this article; also, I will present the case for what I think is the mofA: persuasive interpretation of the Northeast problem.